Effectiveness of triethylene glycol disinfection on airborne MS2 bacteriophage under diverse building operational parameters - Zuraimi Sultan; Irvan Luhung; Ngu War Aung; Akira Uchida; Arulmani Natarajan; Santhi Puramadathil; Jiayu Li; Stephan Schuster; Stefano Schiavon (Indoor Environments)
Research on triethylene glycol (TEG) use to disinfect airborne microorganisms have been conducted in non-realistic chamber settings. This study assesses how air temperature, humidity, HVAC settings, and filtration impact TEG's effectiveness in deactivating a common SARS-CoV-2 substitute, MS2 bacteriophage, in a simulated non-occupied office-sized chamber. The chamber was served by a dedicated HVAC system operating at 22.0, 23.5 and 25.0 °C, at 40, 55 and 70 % relative humidity, at 0, 3 and 6 air change per hour (ACH) recirculation, at 0.8, 2.5 and 5.0 ACH outdoor ventilation and at no, MERV8 and MERV14 filtration status. Airborne MS2 log10 reductions in the presence of TEG increased linearly over time and we noted a higher MS2 inactivation rate with higher TEG concentration. The estimated TEG concentration needed for a one-log inactivation of the MS2 within an hour was 0.44 mg/m3. The efficacy of TEG declined with the increase in temperature from 22.0 to 25.0 °C, peaked at 55 % RH, increased with higher recirculation rates but decreased with increasing ventilation rates and higher efficiency filters. The results of our study suggest that the optimum environmental and building conditions for TEG performance is at 22.0 or 23.5 °C air temperature, 55 % relative humidity, 0.8 ACH ventilation rate and 6 ACH recirculation rate. By conducting experiments in simulated office conditions, this study closes significant knowledge gaps in TEG performance application.